Pengaruh Akuntabilitas Dan Transparansi Terhadap Kinerja Pegawai Di Lingkungan Dinas PUPESDM Studi Kasus: BALAI PIALAM DIY - Muhammad Hadyan Fariz Ahnaf; Isti Rahayu (Jurnal Riset Akuntansi, 2023)
The purpose of this research is to find out how the effect of accountability and transparency on employee performance. The location of this research was carried out in the PUPESDM Service Environment, especially the BALAI PIALAM DIY. The method used is quantitative and the technique used is by distributing questionnaires to BALAI PIALAM DIY employees. The results of the study show that accountability and transparency have a positive effect on employee performance. Accountability and transparency do not have a positive effect on employee performance with gender moderation. With the influence of accountability and transparency on employee performance which is optimal, it is hoped that it is necessary to evaluate the results of work programs, because evaluation is a benchmark or reference for agencies to continue to develop and be able to improve the quality of employee performance to become more qualified.